Respuesta :

Answer:

[tex] \boxed{\sf (p + n)(t) = 2t + 14} [/tex]

Given:

[tex] \sf p(t) = 2t + 10 \\ \sf n(t) = 4 [/tex]

To find:

[tex] \sf (f + g)(x) = f(x) + g(x)[/tex]

Step-by-step explanation:

[tex] \sf \implies(f + g)x = f(x) + g(x) \\ \\ \sf \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = (2t + 10) + ( 4) \\ \\ \sf \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = 2t + 10 + 4 \\ \\ \sf \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = 2t + 14 [/tex]